"Less is More′′: Ultra Low LiPF6 Concentrated Electrolyte for Efficient Li‐Ion Batteries. Issue 11 (19th August 2021) - Nikiforidis, Georgios; Anouti, Mérièm
Abstract: In the pursuit of lowering the cost of lithium‐ion (LIB) and lithium‐metal batteries (LMB), we reduced the lithium salt concentration of the electrolyte (i. e., lithium hexafluorophosphate LiPF6 ) to a record low 0.1 mol L −1 LiPF6 . Herein we present the performance of lithium nickel manganese cobalt oxide (NMC), lithium manganese oxide (LMO), lithium iron phosphate (LFP) cathodes together with graphite and lithium metal anodes in a ternary solvent mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and 1, 1, 2, 2‐tetrafluoroethyl 2, 2, 2‐trifluoroethyl ether (TFE) (3EC/7EMC/20TFE, by weight) containing 0.1 mol L −1 LiPF6 . By virtue of the favored ionic associations between Li + and PF6 − in the presence of the TFE together with EC and EMC, the half and full coin cells revealed a robust performance at room temperature with high specific capacities and coulombic efficiencies (>98.5 %) over a wide current range (C/2→2C), high capacity retention, modest energy density (180 to 207 Wh kg −1 depending on the system), extended calendar life (600 h for the Li symmetric cells), and superior operation to cells using commercial carbonate electrolytes (i. e., 1 mol L −1 LiPF6 in EC/EMC, 3/7, v/v). The morphological characterization of the electrodes revealed mild structural degradation, homogenous distribution of the electrode and electrolyte‐based elements, as well as the formation of decomposition products, especially for the graphite anode. Overall, this study attests to the compatibility of low‐concentrated Li salt electrolytes with promising cathode and anode materials for efficient and cost‐effective battery systems. Abstract : Dilute lithium salt electrolyte for LIB : The applicability of an ultra‐low concentrated lithium salt electrolyte containing alkyl carbonate and poly(fluoroether) is investigated by electrochemical, morphological, and physicochemical means for safe and reliable LIBs. The proposed nonflammable electrolyte demonstrated in a range of cathodes and anodes at room temperature a solid performance, modest decomposition, and superior behavior to mainstream LIB electrolytes.